THE EFFECT OF QUALITY AS REVIEWED FROM THE INDICATORS OF COMPETENCY AND WORK COMMITMENT ON THE PERFORMANCE OF THE MERGER OF SPA PARTICIPANT BROKERS AND SPA ORGANIZER TRADERS AS REVIEWED FROM THE INDICATORS OF MARKET CONFIDENCE - Winahyu Saraswati; Enjang Sudarman; Bambang Nurakhim (Jurnal Manajemen Bisnis Dan Organisasi, 2026)
This study aims to determine the effect of quality, as viewed from the indicators of competence and work commitment, on the performance of the merger of SPA participating brokers and SPA organizing traders, as viewed from the market trust indicator. The phenomenon underlying this research is the discovery of the performance of the merger of SPA participating brokers and SPA organizing traders, as viewed from the market trust indicator, which is not optimal. In this study, the author used quantitative research. The population in this study was 145 employees. In this study, the author used a sampling technique using the Slovin formula for 59 people. Data were collected using a closed questionnaire with a Likert scale, and analyzed using multiple linear regression with the help of the SPSS program version 20. The results of the study indicate that the influence of quality, as viewed from the indicators of competence and work commitment, has a positive and significant effect on the performance of the merger of SPA participating brokers and SPA organizing traders, as viewed from the market trust indicator. This study emphasizes the importance of being able to follow up with appropriate policies to be able to optimally increase market trust.